Facile Synthesis of ZnO Nanoparticles for the Photodegradation of Rhodamine-B - Tety Sudiarti; Neng Hani Handayani; Yusuf Rohmatulloh; Silmi Rahma Amelia; Ravli Maulana Yusuf; Atthar Luqman Ivansyah (Jurnal Kimia Sains dan Aplikasi, 2021)
River pollution is a problem that is still very poorly handled. Industrial growth is the most significant contributor to produce this wastewater. The industry produces liquid waste such as dyes that do not meet handling standards because of the high cost. Photocatalyst is way better than other methods such as adsorption, coagulation, fluctuation, and others. However, there are still many shortcomings of the existing methods, such as high cost, high temperature, and dangerous by-products. This research seeks to provide a solution by synthesizing zinc oxide (ZnO) nanoparticles as a photocatalyst to reduce rhodamine B dye under visible light irradiation. ZnO nanoparticles were successfully synthesized through a simple sol-gel method in the form of a white powder by heating at a low temperature, 60°C. The XRD results show that the results have a diffraction peak that follows the standard ZnO with a hexagonal wurtzite crystal structure. According to the Scherrer equation, the crystal has a size of 22.61 nm. SEM analysis showed that the particle morphology and particle size were homogeneous with a spherical shape, ranging from 22-24 nm. Optimal ZnO photocatalytic activity at 90 minutes with an efficiency of 98.83%.